Isolation and purification of plant secondary metabolites using column-chromatographic technique (Bangladesh Journal of Pharmacology, 2016)
Chromatographic techniques have significant role in natural products chemistry as well as contribute dramatically in the discovery of novel and innovative compounds of pharmaceutical and biomedical importance. This study focused on step-by-step visual demonstration of fractionation and isolation of biologically active plant secondary metabolites using column-chromatographic techniques. Isolation of bioactive compounds using column-chromatographic involves: a) Preparation of sample; b) Packing of column; c) Pouring of sample into the column; d) Elution of fractions; and e) Analysis of each fractions using thin layer chromatography. However, depending on nature of research, compounds can be further purified using high performance liquid chromatography (HPLC), and nuclear magnetic resonance (NMR) spectral analyses.Video Clips of Methodology:Part 1: 3 min 45 sec   Full Screen   AlternatePart 2: 6 min 21 sec   Full Screen   AlternatePart 3: 4 min 45 sec   Full Screen   Alternate